'I hear and I forget. I see and I remember. I do and I understand.'– incorporating high-fidelity medical simulation into the undergraduate nephrology course. Issue 1 (9th November 2020) - Pawłowicz, Ewa; Kulesza, Michelle; Szymańska, Aleksandra; Masajtis-Zagajewska, Anna; Bartczak, Maria; Nowicki, Michał
Abstract: Background: Medical simulation is a teaching method, which enables the development of clinical skills by implementing a simulation scenario in a true-to-life environment, but without exposing patients to any risk. So far, there has been no information on the use of high-fidelity simulation in undergraduate clinical nephrology teaching. Aim of this study was to analyze students' opinions and reactions to the simulation module in nephrology. Methods: The survey consisting of the Satisfaction with Simulation Experience Scale (SSES) and open-ended question concerning the overall impression of classes was conducted among 103 5 th year medical students, who took part in the simulation training in nephrology. SSES consisted of three parts (debriefing, reasoning, education). Statements from the open-ended question were interpreted by means of the Atlas.ti software for qualitative data analysis. Results: The overall score for simulation classes was 4.39 ± 0.69 points. Students rated debriefing, reasoning and education at 4.43 ± 0.78, 4.32 ± 0.7 and 4.39 ± 0.73 points, respectively. 87.4% and 84.5% of participants agreed that simulation developed their 'clinical reasoning' and 'decision-making' skills in nephrology, respectively. Thematic analysis revealed that students evaluated the module as 'interesting', 'useful' and 'informative', but they found number of classes significantly insufficient. Students pointed out that due to the small emphasis placed on practical aspects in the existing curriculum e.g. routes of drug administration and conversion of doses, they could not fully benefit from simulation. Conclusion: Medical simulation is a valuable constituent of the nephrology course. Putting greater emphasis on practical aspects from the beginning of training may enable students to benefit more from simulation modules.